Recycling of domestic wastewater treated by vertical-flow wetlands for irrigation of two consecutive Capsicum annuum generations - Almuktar, Suhad A.A.A.N.; Abed, Suhail N.; Scholz, Miklas (Ecological engineering, 2017)
[Display omitted] •Phosphorus, ammonia, potassium and coliforms exceeded the irrigation thresholds.•Highest fruit numbers link to small aggregates, short resting and contact times.•Diluted inflow wastewater is linked to high fruit numbers.•High inflow load: good yield for small aggregates and long contact/resting times.•Load reductions for the first generation plants resulted in high fruit numbers. Due to water scarcity, there is great interest in reusing various nutrient-rich wastewaters. The aim of this article is consequently to evaluate if domestic wastewater treated by various wetland systems can be successfully recycled to irrigate generations of commercial crops such as Chilli (Capsicum annuum) grown in compost within a laboratory environment to obtain a cultivar adapted to domestic wastewater. The corresponding objectives were to assess the irrigation water for long-term growth when applying recycled wastewater, the impact of various wastewaters subject to the wetland characteristics, the impact of treated wastewater volume for irrigation, and the economic return of different experimental set-ups in terms of marketable yields. The vertical-flow wetlands treated domestic wastewater well, meeting the irrigation water quality standards for most water quality parameters, except for phosphorus (4.2±0.48mg/l), ammonia-nitrogen (4.2±2.64mg/l), potassium (7.0±3.03mg/l) and total coliforms (69647±64852.6CFU/100ml), which showed high values significantly (p<0.05) exceeding common thresholds set for irrigation applications of 2mg/l, 5mg/l, 2mg/l, and 1000CFU/100ml. Chilli generations were grown successfully when applying wastewater treated by wetlands and organic soil. High Chilli generation yields concerning economic return were linked with wetlands containing small aggregates with long contact and resting times and fed with a high inflow loading rate (undiluted wastewater), releasing more nutrients into their effluent producing the best fruit quality with respect to weight, length and width resulting in a greater marketable profit of about 46% compared with the others. First generation Chilli plants were grown with considerably shorter heights and produced abundant fruit numbers, which were harvested earlier than their mothers due to the reduction (approximately 55%) of irrigation water volume used for them compared to their mothers. However, excessive nutrients applied on mother plants via irrigation water resulted in better fruit quality regarding dimensions and weights compared with their corresponding first generation plants, leading to a greater marketable profit by about 25%.